Reduced fatigue in passive versus active recovery: An examination of repeated-change-of-direction sprints in basketball players - Madueno, M. C.; Dalbo, V. J.; Guy, J. H.; Giamarelos, K. E.; Spiteri, T.; Scanlan, A. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To investigate the physiological and performance effects of active and passive recovery between repeated-change-of-direction sprints. Methods: Eight semiprofessional basketball players (age: 19.9 [1.5] y; stature: 183.0 [9.6] cm; body mass: 77.7 [16.9] kg; body fat: 11.8% [6.3%]; and peak oxygen consumption: 46.1 [7.6] mL/kg·min) completed 12×20-m repeated-change-of-direction sprints (Agility 5-0-5 tests) interspersed with 20 seconds of active (50% maximal aerobic speed) or passive recovery in a randomized crossover design. Physiological and perceptual measures included heart rate, oxygen consumption, blood lactate concentration, and rating of perceived exertion. Change-of-direction speed was measured during each sprint using the change-of-direction deficit (CODD), with summed CODD time and CODD decrement calculated as performance measures. Results: Average heart rate (7.3 [6.4] beats·min-1; P=.010; effect size (ES)=1.09; very likely) and oxygen consumption (4.4 [5.0] mL/kg·min; P=.12; ES=0.77; unclear) were moderately greater with active recovery compared with passive recovery across sprints. Summed CODD time (0.87 [1.01] s; P=.07; ES=0.76, moderate; likely) and CODD decrement (8.1% [3.7%]; P<.01; ES=1.94, large; almost certainly) were higher with active compared with passive recovery. Trivial-small differences were evident for rating of perceived exertion (P=.516; ES=0.19; unclear) and posttest blood lactate concentration (P=.29; ES=0.40; unclear) between recovery modes. Conclusions: Passive recovery between repeated-change-of-direction sprints may reduce the physiological stress and fatigue encountered compared with active recovery in basketball players.